YORUBA SACRED MUSIC FROM EKITI by ANTHONY KING, Ibadan University Press, Nigeria, 1961, pp. x, 46, xlix (text and music), 8 half-tone illustrations, 8½" x 5½" - Mackay, Mercedes (International Library of African Music, 1961)
pages: 105
Keywords: Yoruba (African people); Sacred music; African Music; Nigeria; Yoruba Art